Pelatihan Hypnosis Untuk Meregulasi Stres Dalam Lingkungan Kerja Anggota Sabhara Polda Sulawesi Selatan - Ahmad Razak; Saiid Irham Febrian; Nur Maghfira Nisza; Husniah Husniah; Merna Karlely; Nurul Istiqamah (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Work stress is a feeling of pressure or a sense of pressure experienced by employees in facing their work. Hypnonsis according to Muhammad Noer is a method of communicating, both verbal and non-verbal, which is persuasive and secresive to a person so that he becomes creative and then reacts according to the basic spiritual value system that a person has. The method of implementation to sabhara members by conducting hypnotherapy training with the theme "introduction of hypnosis". The training was conducted offline at the Bag Psi Hall of the South Sulawesi Regional Police. Evaluations are given to assess participants' knowledge before and after being given training. The subjects of 30 were members of the sabhara. Based on the results of the pre-test and post-test of psychoeducational participants at the South Sulawesi Regional Police, it showed an increase from the average pre-test score of the participants, namely 2.96, then after training, the average post-test value of the participants increased to 5.63 with an increase of 2.66. This shows an increase in the number of participants' knowledge and understanding of psychoeducation regarding hypnosis.